A Scoping Review to Evaluate the Clinical Efficacy of Indigenously Produced, Patient-Specific Acrylic Cranial Prosthesis in Decompressive Craniectomy in India - Charu Guleria; Shrish Nalin; Dinesh Kumar (Indian Journal of Neurosurgery)
Health Technology Assessment in India assesses, evaluates, and carries out cost-effectiveness of available health technologies in the country for evidence-based decision-making. Current study carried out a scoping review to assess clinical efficacy of poly-methyl-methacrylate (PMMA) after decompressive craniectomy using various prototyping techniques in published literature. The O'Malley methodology and Preferred Reporting Items for Systematic Reviews and Metanalysis for Scoping Reviews—PRISMA-ScR—checklist were used to assess published literature from year 2008 to 2023. A total of 507 records were identified after searching electronic databases. After removing duplicate studies and studies that did not meet inclusion criteria, a total of 12 studies were included for review. A total of four studies were described as experimental and eight were case reports/series. The sample size of intervention studies varied between 10 and 30 patients with a mean age of 36.7 years. In a total of seven studies, cranioplasty was done by a self-made PMMA prosthesis fabricated using a novel three-dimensional-printed cranial model fabrication technique. In experimental study, objective criteria like operative Glasgow Outcome Scale, Cranial Index of Symmetry score, and Visual Analog Score for Cosmesis were employed. Clinical assessment for cranial symmetry was observed favorable for PMMA with fewer complications, though sample size was inadequate (range: 10–30) with comparator group in two studies.